If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 = 7 + -3x Reorder the terms: -4 + 4x = 7 + -3x Solving -4 + 4x = 7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + 4x + 3x = 7 + -3x + 3x Combine like terms: 4x + 3x = 7x -4 + 7x = 7 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + 7x = 7 + 0 -4 + 7x = 7 Add '4' to each side of the equation. -4 + 4 + 7x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = 7 + 4 7x = 7 + 4 Combine like terms: 7 + 4 = 11 7x = 11 Divide each side by '7'. x = 1.571428571 Simplifying x = 1.571428571
| 4(x-8)+=-10 | | -15g-13g=54 | | 7.7+-0.1c= | | 7m+3=-73 | | -7.2-(2.8-7n)=2.6 | | b^2=4b^2-144 | | 8.95+g-8.95=11.45+8.65 | | 2y=34 | | 2(-6+z)-(-8z+10)= | | 0=20+p | | 6ln(3x)=42 | | -7(2y-4)= | | (8-2x)(15-2x)(x)=0 | | 6(x-9)= | | 4y+2=182-4x | | 9+6x=10+9x | | -x+7+3=4(x+2)-5 | | 6b-10b-3b= | | abc+bca=cab | | 0=(x-5)(2x-1) | | 36X+81= | | 26X+81= | | 3k^2-18x-21=0 | | 3x-10=-x+12-4x | | p-2sqrtp=8 | | 3x^2y-2y^3+1=4xy^4 | | Y-(12+9)=47 | | m^2-127=0 | | 2x+2x=-9.0+2x | | 5x+2-4=8x+2-8 | | 7-(2X+5)=25-5X | | 6x-7(-1+x)=8 |